2016
DOI: 10.1038/srep29901
|View full text |Cite
|
Sign up to set email alerts
|

Apollo Lunar Astronauts Show Higher Cardiovascular Disease Mortality: Possible Deep Space Radiation Effects on the Vascular Endothelium

Abstract: As multiple spacefaring nations contemplate extended manned missions to Mars and the Moon, health risks could be elevated as travel goes beyond the Earth’s protective magnetosphere into the more intense deep space radiation environment. The primary purpose of this study was to determine whether mortality rates due to cardiovascular disease (CVD), cancer, accidents and all other causes of death differ in (1) astronauts who never flew orbital missions in space, (2) astronauts who flew only in low Earth orbit (LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
143
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(150 citation statements)
references
References 37 publications
0
143
0
7
Order By: Relevance
“…On the other hand, an economic-technological system that essentially seeks to optimize profit as a synonym of well-being and, by extension, an illusion of happiness. Given the current state of the biosphere [75][76][77], would we expect another result? The complexity of this disjunctive is that nothing is more proper to human nature than its willingness to learn.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, an economic-technological system that essentially seeks to optimize profit as a synonym of well-being and, by extension, an illusion of happiness. Given the current state of the biosphere [75][76][77], would we expect another result? The complexity of this disjunctive is that nothing is more proper to human nature than its willingness to learn.…”
Section: Resultsmentioning
confidence: 99%
“…Humans under stress respond on a physiological level to geomagnetic field variations associated with space storms, as reported by Breus and Rapoport (2003). Ionizing radiation is also thought to be responsible for a higher incidence of adverse cardiovascular events (Delp et al 2016). And there appear also to be space weather-related seasonal influences on the human heart (Cornélissen et al 2002; Kleimenova et al 2008; Mavromichalaki et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, PMRs demonstrated that a higher proportion of lunar astronauts died of CVD than either of the comparison groups, leading the authors to conclude that lunar astronauts were at greater risk of death by CVD than astronauts who had never left low Earth orbit or never flown into space at all. Conflating these findings with a model of how radiation may damage vascular endothelial tissue in rats, the authors proposed a potential biological mechanism to match their purported epidemiologic findings [14].…”
Section: Lunar Astronaut Mortality From Cvdmentioning
confidence: 99%
“…In 2016, a published study investigated the risk of CVD mortality for astronauts who had either walked on the moon or who completed circumlunar flights as part of the Apollo missions (so-called lunar astronauts) [14]. The study compared lunar astronauts to astronauts who only completed missions on low Earth orbit (LEO), or to astronauts who had not flown to space at all ("nonflight" astronauts).…”
Section: Lunar Astronaut Mortality From Cvdmentioning
confidence: 99%
See 1 more Smart Citation